Mapping China's freshwater fishes: diversity and biogeography. Issue 2 (10th January 2013) - Kang, Bin; Deng, Junming; Wu, Yunfei; Chen, Liqiang; Zhang, Jie; Qiu, Haiyuan; Lu, Yin; He, Daming
Abstract Freshwater fishes worldwide face an array of threats from dam construction, river fragmentation, pollution, over‐exploitation and interactions with introduced species. Such impacts are especially prevalent in densely populated countries undergoing rapid development, and their effects are felt most strongly where regional fish diversity is high. We reviewed studies of the distribution of freshwater fish species throughout China to map a biogeographical pattern and ascertain the environmental factors contributing to this distribution. We then linked this information to identify geographic areas to be recommended as the focus of conservation efforts. A total of 920 species in 302 genera, 54 families and 21 orders were recorded. Among the recorded species, 73% were Cypriniformes and 12% were Siluriformes. Cyprinidae was the most dominant family with 473 species, followed by Balitoridae with 157 species. The administrative division of the biogeography of China's freshwater fishes consisted of nine regions, including the Qinghai‐Tibetan Plateau Region, Oriental Region, Northwest Region, South Region, Loess Plateau Region, Heilongjiang Region, Upper Yangtze Region, 3H Plain Region and Middle‐Lower Yangtze Plain Region. The river system was the primary factor in determining China's freshwater fish biogeography. Under stepwise regression analysis, river discharge was found to be the most influential factor in determining richness, followed by population size and net primary productivity. The higher level of fish endemicity and sensitivity to environmental change led to the identification of Southwest China and the higher areas of Qinghai‐Tibetan Plateau as the primary areas to be considered for fish conservation and potential natural reserves.